A CLINICAL STUDY ON MANAGEMENT OF STRESS IN TYPE -2 DIABETES MELLITUS (MADHUMEHA) WITH ASHWAGANDHA (WITHANIA SOMNIFERA) (AYUSHDHARA, 2016)
Extensive worldwide research on diabetes has established the complexities of the relationship between stress and diabetes. Evidence suggests that stress can affect diabetes, in terms of both its onset and exacerbation. Stress can have a deleterious effect on glycaemic control and can affect quality of life in diabetics. On the other hand emerging evidence strongly suggests that interventions that help individuals prevent or cope with stress can have an important positive effect on quality of life and glycaemic control.In this clinical study we have approached to assess the different stresses like Emotional burden, Physician related distress, Regimen related distress & Interpersonal distress in Type – 2 diabetic populations with Diabetes Distress Scale (DDS). Those diabetics having a considerable stress level (DDS Score > 3) were given treatment with Ashwagandha (Withania somnifera) capsules for six weeks and once again their stress level was reassessed.Ashwagandha significantly reduced the stress level and other stress related complains along with a better glycemic control as compared to placebo without any adverse effect. The positive effect of the drug also continued for another six weeks even after withdrawing the medication.Therefore Ashwagandha can offer comprehensive benefits as an adjuvant in Type – 2 diabetics suffering from stress.